Evaluating the Psychometric Properties of the Teamwork KSA Test. (December 2015) - French, Kimberly A.; Kottke, Janet L.; Kirchner, Rhiannon J.
Abstract : The Teamwork KSA Test has been a welcome addition to the practitioner's selection toolkit as well as a useful measure for teamwork researchers. We analyzed the psychometric properties of the Teamwork KSA Test and recognized correlates of the construct using three samples of working individuals recruited through a university ( N = 241, N = 230, N = 332) and found slim evidence for a factor structure of the underlying constructs. Furthermore, classical reliability estimates did not meet traditional psychometric standards. Total TKSA scores predicted self‐ratings and instructor ratings of teamwork in two of the samples; effect sizes were small.